Longman dictionary of English idioms - Long, T. H. (Harlow [Eng.] : Longman, 1979)
The Longman Dictionary of English Idioms is a complete and up-to-date guide to the meaning, grammar, and typical use of the most common idiomatic phrases in English. Over 4500 idioms.
Text on lining papers.
oif 08/02/2019
Ref.
Keywords: English language; English language idioms